Fixation : how to have stuff without breaking the planet - Goldmark, Sandra (Island Press, 2020)
"Sandra Goldmark was a new mother, short on sleep and closet space, when her vacuum broke. And her toaster. And the strap on her backpack. Objects that were supposed to make her life easier instead piled up inside her family's small apartment, broken and collecting dust. Goldmark didn't want a new vacuum or toaster--she wanted the ones she had to work. But the reality is that the systems through which we obtain our stuff are vast and entrenched, with products designed for quick replacement, not repair. Most of would have given up and turned to Amazon.com, but Goldmark imagined a different, better future--one where having stuff is simpler, healthier, and more sustainable for people and the planet. Determined to find a better way, she founded a series of pop-up repair shops with her husband and began to learn more about the way we make and use things, and how those things help make us who we are. Fixation is not a repair manual, nor will it tell you how to declutter your closet. Instead, it takes readers on a quest to radically reimagine what a healthy relationship with our stuff might look like. Along the way, Goldmark shows us how individuals can adopt more thoughtful patterns of personal consumption, businesses can develop healthy models for growth, and together we can demand social and political change that will move us to a more sustainable and equitable circular economy"--Insde jacket.